Insurgency and Counterisurgency in Afghanistan - Ramazanova, Aynur (ADA University, 2013)
It is more than 3 5 years that Afghanistan is striving for security, stability and development. However, insurgency, an organized revolt against the government with the purpose of getting access to political power, undermines all the efforts. As time passed, insurgency evolved, changing the nature from jihadist movement to civil war of mujahedeen, and then again using religious umbrella. The Soviet-backed communist government failed to eradicate insurgency, so does the current government backed by a large number of states, mainly NATO members. The operations started in 2001, in the aftermath of 9/11, and were in drawing the Taliban out of the country. The Taliban and associated insurgent groups have found sanctuaries on the Pakistani territory, and still operate from there. In 2009 the coalition started the counterinsurgency (COIN) campaign in Afghanistan, recalling a more or less successful experience in Iraq. The emphasis of a new approach was on more targeted military operations and importance of population, which was previously ignored. The ISAF mission, created in December 2001, and led by NATO since 2003, comes to its end by the end of 2014. The states are driving their forces out, relying on the assumption that the training given to Afghan National Security Forces (ANSF) was enough for them to be sustainable in maintaining security in the country. However, the real situation does not yield so much optimism. There many challenges faced by allies today and not yet addressed. The COIN efforts seem to be ineffective and unsuccessful, but one should not hurry to criticize the approach. A thorough analysis helps to define the reasons of failure of COIN campaign, as well as shows their strong connectedness to the causes of insurgency.
Keywords: Public and International Affairs; Afghanistan -- History -- 2001-; Afghan War, 2001-; Afghanistan -- NATO; Afghanistan -- ISAF